(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2016)
The article examines the formal definition of the social and economic responsibility, which implies the duty of management to make decisions and take actions that improve the use of natural resources and the interests of both society and the organization. All companies are accountable to the state for compliance with current legislation regarding industrial activity. This primarily concerns ensuring that quality parameters of products with existing standards and certificates, pricing policy – the rules of competition titles and others.